Did the US stage a lie on 9/11? - Abd Razak, Dzulkifli (2006)
Questions are still being raised over 9/11 and what actually transpired then. The socalled ‘war on terror’ and detention of hundreds of people have caused worldwide anger. FIVE years after the 9/11 tragedy, some "cracks" are beginning to appear. The collapse of the World Trade Center was not as straight forward as it has been made out to be. For one, it has spawned even more cruelty and abuse, with wideranging forms of punishment meted out to just anyone who qualifies under the vague label of "enemy combatants", including those who happened to be in the wrong place at the wrong time.